Within the Margin of Error Derogations, Limitations, & the Advancement of Human Rights - Fernandez, Gemmo Bautista (Philippine Law Journal, 2019)
The article examines the effects of derogation and limitations clauses embodied in human rights instruments. The former allow for temporary deviations that limit or detract from the rights provided by human rights instruments while the latter constitute justifiable restrictions on the exercise of certain rights guaranteed by human rights instruments. In theory, these clauses, collectively referred to as 'special measures', aim to strike a balance between the individual's rights and obligations of the state. However, while they have the capacity to advance human rights in theory, the use of these measures has been problematic in practice. The article delves into the rationale and practice surrounding the taking of the right to derogate and the imposition of limitations. It considers the necessity of the inclusion of these measures in human rights instruments. It examines how they affect the implementation of the rights embodied therein. Lastly, it analyses the effectiveness of the safeguards against abuse. The article notes that the standards for assessing the validity of measures taken by governments and the procedure for monitoring compliance have to be re-evaluated. Moreover, it considers the need for greater institutional oversight.